2023
DOI: 10.52866/ijcsm.2023.02.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Abnormal Driving Behavior Using Modified DenseNet

Aisha Ayad,
Matheel E Abdulmunim

Abstract: Car accidents have serious consequences, including depletion of resources, harm to human health and well-being, and social problems. The three primary factors contributing to car accidents are driver error, external factors, and vehicle-related factors. The main objective of this paper is to address the issue of car accidents caused by driver error. To achieve this goal, a solution is proposed in the form of a modified version of the Dense model, called the 1Dimention-DenseNet, specifically designed to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Te use cases for digital picture segmentation are numerous, as are the types of images that can be segmented. In this research, we propose an improved version of DenseNet [13] (TLDenseNet)-one of the best CNN models-by integrating the transfer learning mechanism to better handle pictures with varying attributes and segmentation needs. Figure 5 depicts the basic idea behind this model-based approach to digital picture segmentation.…”
Section: Image Segmentation Based On Tldensenet Modelmentioning
confidence: 99%
“…Te use cases for digital picture segmentation are numerous, as are the types of images that can be segmented. In this research, we propose an improved version of DenseNet [13] (TLDenseNet)-one of the best CNN models-by integrating the transfer learning mechanism to better handle pictures with varying attributes and segmentation needs. Figure 5 depicts the basic idea behind this model-based approach to digital picture segmentation.…”
Section: Image Segmentation Based On Tldensenet Modelmentioning
confidence: 99%
“…Another study also observed and assessed driver control and safe practices during the process of driving a vehicle using risky driving behavior as the research variable [16]. Moreover, Mafeni [17] and Takashi Bando [18] evaluated driving behavior errors with a focus on abnormal braking and vehicle speed operation when traveling at very high speeds. It was also observed that even though the studies have different objectives, none focused on energy consumption in evaluating driving behavior.…”
Section: Introductionmentioning
confidence: 99%